2012
DOI: 10.1167/iovs.12-9659
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vessel Oxygen Saturation under Flicker Light Stimulation in Patients with Nonproliferative Diabetic Retinopathy

Abstract: PURPOSE. We investigated the response of retinal vessel diameters and oxygen saturation to flicker light stimulation of neuronal activity in patients with diabetic retinopathy. METHODS.We included 18 patients with nonproliferative diabetic retinopathy (mean age 62.2 6 8.3 years, diabetes type 1 in 4 patients and type 2 in 14, hemoglobin A1c 7.7 6 0.9%, duration of diabetes 24.1 6 9.3 years) and 20 agematched healthy controls (age 66.7 6 10.3 years). Dual wavelength (548 and 610 nm) fundus images were taken bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…In contrast, a decrease in O 2 tension (hypoxia) induces a dilation of the retinal arterioles and an increase in blood flow (Eperon et al 1975;Pournaras et al 2008 (Weinreb and Harris 2009). Several studies have shown that the vasodilation response to flicker stimulation is impaired in pathological conditions, including glaucoma (Ramm et al 2014), diabetic retinopathy (Hammer et al 2012) and vasospastic propensity (Gugleta et al 2006). Our model suggests that the observed vasodilation in the retinal arterioles might be due to an O 2 -mediated response (Arciero et al 2013;Pournaras et al 2008).…”
Section: Simulation Results In Baseline Conditionsmentioning
confidence: 56%
“…In contrast, a decrease in O 2 tension (hypoxia) induces a dilation of the retinal arterioles and an increase in blood flow (Eperon et al 1975;Pournaras et al 2008 (Weinreb and Harris 2009). Several studies have shown that the vasodilation response to flicker stimulation is impaired in pathological conditions, including glaucoma (Ramm et al 2014), diabetic retinopathy (Hammer et al 2012) and vasospastic propensity (Gugleta et al 2006). Our model suggests that the observed vasodilation in the retinal arterioles might be due to an O 2 -mediated response (Arciero et al 2013;Pournaras et al 2008).…”
Section: Simulation Results In Baseline Conditionsmentioning
confidence: 56%
“…In addition, retinal oxygen tone is tightly controlled by autoregulation of the vessel diameters [95]. These data, together with impaired flicker light-induced vasodilation in diabetes, lend support to the hypothesis of an impaired regulation of oxygen supply to the diabetic retina [96].…”
Section: Assessing Functional Changes Of the Retinal Microvasculaturementioning
confidence: 61%
“…8 Briefly, fundus images with the optic nerve head in center were taken. Oxygen saturation was measured in all vessels in a peripapillary annulus, with an inner radius of 1 and an outer radius of 1.5 disc diameters and averaged over all arterioles and venules.…”
Section: Measurement Of Retinal Oxygen Saturationmentioning
confidence: 99%